2011
DOI: 10.1007/s12374-011-9162-y
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Analysis of Leaf Responses to Enhanced Ultraviolet-B Radiation in Two Rice (Oryza sativa L.) Cultivars Differing in UV Sensitivity

Abstract: To determine the proteomic response to UV irradiation, two cultivars, i.e., Lemont (UV tolerant) and Dular (UV sensitive), were exposed to natural and enhanced ultraviolet-B (UV-B) irradiation for 1, 7, and 14 days, and two-dimensional gel electrophoresis in combination with mass spectrometry (MS) and bioinformatics were used to compare the different proteomic responses in the leaves of the two cultivars. Thirty-nine proteins were up-or downregulated following the UV-B treatments. Among them, 30 increased or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…4). During recent proteomic studies on Oryza sativa (Wu et al, 2011), 39 proteins upor downregulated, following the UV-B radiation, have been identified. These identified proteins were mostly upregulated in UV-B-tolerant cultivars of rice, while less than half of them were downregulated in UV-B-sensitive cultivars of rice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4). During recent proteomic studies on Oryza sativa (Wu et al, 2011), 39 proteins upor downregulated, following the UV-B radiation, have been identified. These identified proteins were mostly upregulated in UV-B-tolerant cultivars of rice, while less than half of them were downregulated in UV-B-sensitive cultivars of rice.…”
Section: Resultsmentioning
confidence: 99%
“…In response to stressors, plant mobilizes various protective materials: antioxidant enzymes, signal and PRproteins, flavonoids and phenylpropanoids, hormones, and this feature can be applied to increase the synthesis of plant-produced biologically valuable materials; however, the response and stress-induced effects depend on the plant species, intraspecific diversity, and genotype characteristics (Kalbina, Strid, 2006;Wu et al, 2011;Baroniya et al, 2013). In our previous studies we demonstrated that interspecific somatic potato hybrids resistant to cold after UV-B 8 kJ m -2 d -1 dose exposure, induced two new SOD isoforms, indicating that hybrids are also more tolerant to another environmental factor -UV-B radiation (Vyšniauskienė et al, 2007).…”
Section: Effect Of Uv-b Radiation On Growth and Antioxidative Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…UV-B radiation may affect N cycling in ecosystems by decreasing mobilization of N into biomass, photosynthesis, the decomposition rate of litter and the N concentration of plants (Moody et al, 2001;Wu et al, 2011). Moreover, reports about intraspecific responses in N metabolism of plants to enhanced ultraviolet-B radiation under field conditions are limited.…”
Section: Ajesmentioning
confidence: 99%